Continuous dynamic monitoring of a prestressed concrete bridge based on strain, inclination and crack measurements over a 14-year span. (September 2018) - Hu, Wei-Hua; Said, Samir; Rohrmann, Rolf G; Cunha, Álvaro; Teng, Jun
The Westend Bridge is located on the A100 Highway in Berlin. An integrated continuous dynamic monitoring system, composed of 20 velocity sensors, 5 temperature sensors, 3 strain gauges, 2 inclination sensors and 1 crack sensor was implemented by the Federal Institute for Materials Research and Testing (BAM) in 2000. The system runs continuously with occasional intermittence and leads to a huge amount of data over a 14-year span. In this article, variations of the strain, crack and inclination measurements during the last 14 years are presented. It is noted that the observed crack and inclination of the bridge are strongly influenced by seasonal temperature variation. It further induces change in the relationship between the strains measured in both concrete and prestressed tendon. Application of k -means cluster analysis technique in both the crack and strain measurements can partition them into different seasonal phases by identifying 'turning points' that indicate annual periodical bridge change. In the period of these two 'turning points', a strong linear relation of the strains in two materials is observed. In the rest of the year, a nonlinear relationship between the strains recorded in both the concrete and the prestressed tendon is noted. The possible reason is the additional thermal load due to the change in temperature difference between the bridge's surface and soffit. Finally, a health index in a framework of regression model and process control theory is proposed by investigating the linear relationship between the strains in concrete and prestressed tendon. The tendency of the health index in the 14 years may suggest the long-term bridge change during that time frame.